LEARNING STYLES IN THE BRAIN A LOOK FROM THE ROLE OF INSTRUCTOR - Bolívar Brito, José Alfonso
The objective of this article was to have an approach in relation to the learning styles and the training process developed by SENA. For this, a descriptive methodology with a demographic approach was used, where the first action undertaken was to determine the psychographic characteristics of the trainees of the document management technologist; developing a series of steps. The results showed that the learner is unaware of their own learning style and how to take advantage of them in their studies. It is concluded that, from the researcher's point of view, the subject of learning styles within the institution should be reviewed, since, when designing teaching strategies, the learning strategies that each individual possesses must be taken into account. Being decisive for the instructor to learn from the apprentices, in accordance with the evaluation criteria contemplated in their training program and the requirements demanded by SENA.